Interaction of smoking and atopy in producing specific IgE antibody against a hapten protein conjugate. - Venables, K M (1985)
A survey was carried out of a population of workers exposed to tetrachlorophthalic anhydride, an acid anhydride epoxy resin curing agent known to cause asthma. Using a radioallergosorbent test with a tetrachlorophthalic anhydride human serum albumin conjugate, specific IgE antibody was detected in serum from 24 out of 300 factory floor workers exposed to tetrachlorophthalic anhydride. Of these 24, 20 (83.3%) were current smokers compared with 133 (48.2%) of 276 without antibody (p less than 0.01), and there was a weaker association with atopy, defined by skin tests with common allergens. Smoking and atopy interacted, the prevalence of antibody being 16.1% in atopic smokers, 11.7% in non-atopic smokers, 8.3% in atopic non-smokers, and nil in non-atopic non-smokers (p less than 0.025). Smoking may predispose to, and interact with atopy in, the production of specific IgE antibody to this hapten protein conjugate.